Locating-Chromatic Number of Amalgamation of Stars - Asmiati Asmiati; H. Assiyatun; E. T. Baskoro (Institute for Research and Community Services (LPPM) ITB, 2011)
Let G be a connected graph and c a proper coloring of G . For i Æ’1,2,Æ’»,k define the color class i C as the set of vertices receiving color i . The color code c (v)